Pengaruh Penerapan Proyek PAQ terhadap Literasi STEM Aspek Sikap pada Topik Pemanasan Global dalam Masa Pandemi Covid-19 - Rivana Usgianti Tanti (JURNAL RISET INDRAGIRI, 2022)
The Covid-19 pandemic that has hit the world has also affected changes in the education system in Indonesia. Not all schools have the ability to implement online learning which requires an internet network and a set of advanced media. Schools located in areas with limited internet networks, poor community economic conditions, and the difficulty of reaching students' residences as in SMP Negeri 1 Batang Tuaka require special efforts from teachers to create the most realistic learning innovations for students. This study aimed to determine the effect of the use of the Al-Qur'an Verse Search project (PAQ) on improving STEM literacy on the attitude aspect on the topic of Global Warming at SMP Negeri 1 Batang Tuaka during the Covid-19 pandemic. This research was a quasi-experimental study with 36 students of class VII at SMP Negeri 1 Batang Tuaka in the 2021/2022 academic year which is divided into two classes, namely the control class and the experimental class. The instrument of this research is the attitude of students' interest in STEM and students' concern for the environment. Data were analyzed using SPSS 22 and the "effect size" calculator. The results of the study indicated that the application of STEM learning through the Al-Quran Verse Search (PAQ) project had a large effect on improving student interest in STEM. Attitude indicators showing curiosity about issues related to STEM and considering a career in the STEM field were significantly different with a 2-tailed sig of 0.00 (sig <0.05) between classes that applied PjBL-STEM and classes that applied PjBL without a STEM approach. At the attitude indicator, awareness of environmental health problems that applied PjBL without a STEM approach, the results show a significant difference with a 2-tailed sig of 0.010 and an effect size in the medium category (medium effect), while the indicators of student perceptions of environmental health issues are not significantly different (sig 2-tailed 0.088 and 0.179) between classes that applied PjBL-STEM and classes that applied PjBL without STEM approach. Keywords : PAQ project, STEM literacy, attitude, interest, environmental care